Identification of peptide‐binding sites within BSA using rapid, laser‐induced covalent cross‐linking combined with high‐performance mass spectrometry. Issue 2 (10th October 2017) - Hauser, Melinda; Qian, Chen; King, Steven T.; Kauffman, Sarah; Naider, Fred; Hettich, Robert L.; Becker, Jeffrey M.
Abstract: We are developing a rapid, time‐resolved method using laser‐activated cross‐linking to capture protein‐peptide interactions as a means to interrogate the interaction of serum proteins as delivery systems for peptides and other molecules. A model system was established to investigate the interactions between bovine serum albumin (BSA) and 2 peptides, the tridecapeptide budding‐yeast mating pheromone (α‐factor) and the decapeptide human gonadotropin‐releasing hormone (GnRH). Cross‐linking of α‐factor, using a biotinylated, photoactivatable p ‐benzoyl‐L‐phenylalanine (Bpa)–modified analog, was energy‐dependent and achieved within seconds of laser irradiation. Protein blotting with an avidin probe was used to detect biotinylated species in the BSA‐peptide complex. The cross‐linked complex was trypsinized and then interrogated with nano‐LC–MS/MS to identify the peptide cross‐links. Cross‐linking was greatly facilitated by Bpa in the peptide, but some cross‐linking occurred at higher laser powers and high concentrations of a non‐Bpa–modified α‐factor. This was supported by experiments using GnRH, a peptide with sequence homology to α‐factor, which was likewise found to be cross‐linked to BSA by laser irradiation. Analysis of peptides in the mass spectra showed that the binding site for both α‐factor and GnRH was in the BSA pocket defined previously as the site for fatty acid binding. This model system validates the use of laser‐activation to facilitate cross‐linking of Bpa‐containing molecules to proteins. The rapid cross‐linking procedure and high performance of MS/MS to identify cross‐links provides a method to interrogate protein‐peptide interactions in a living cell in a time‐resolved manner. Abstract : A biotinylated, photoactivatable p‐ benzoyl‐L‐phenylalanine–modified peptide was cross‐linked within seconds of ultraviolet laser irradiation into the cleft between domains I and III of BSA. To test whether this model could be extended to use with native peptides, gonadotropin‐releasing hormone was similarly irradiated and found to cross‐link into the same domain. The rapid irradiation coupled with high performance of MS/MS to identify cross‐linked products provides a method to interrogate protein‐peptide interactions in a living cell in a time‐resolved manner.